Pengaruh Lama Penyimpanan Serum Kontrol Darah Sapi Pada Suhu -200c Terhadap Kadar Protein Total - Wirdullutfi, Wirdullutfi; Hijriani, Baiq Isti; Sakaroni, Rubiyatna (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2025)
The quality of testing in clinical laboratories is monitored by checking the accuracy of tests using quality control materials. One important parameter to test these materials is total protein measurement. Total protein testing is crucial because it provides an overall indication of liver function. This study aimed to determine the effect of the storage duration of bovine control serum at -20°C on total protein levels. The research used a quasi-experimental design, meaning it did not fully meet the criteria of a true experimental design, as some variables were not completely controlled or manipulated. The collected data were analyzed using a One Way ANOVA test, which compares samples with one category each. The average total protein level before storage was 7.698 g/L. After storage for 1, 2, 3, 4, and 5 weeks, the average levels were 7.693 g/L, 7.696 g/L, 7.700 g/L, 7.705 g/L, and 7.718 g/L, respectively. The One Way ANOVA test showed a between-group frequency of 5 and within-group frequency of 30. The F value was 1.083 with a p-value of 0.390, which is greater than 0.05. This means storage time at -20°C had no significant effect on total protein levels in bovine control serum. Therefore, it can be concluded that the duration of storage under these conditions does not affect total protein concentration.